The multicenter experience with bendamustine in the treatment of relapsed and refractory multiple myeloma - S. V. Voloshin; S. S. Bessmeltsev; T. P. Zagoskina; N. V. Medvedeva; K. D. Kaplanov; E. V. Karyagina; A. D. Garifullin; A. Yu. Kuvshinov; L. V. Stelmashenko; K. M. Abdulkadyrov (Онкогематология, 2015)
Relapsed and refractory (R/R) multiple myeloma (MM) constitutes a specific and unmet medical need. Median survival ranges from as little as 6 to 9 months, and responses to treatment are characteristically short. In patients with R/R MM after therapy of bortezomib and/or immunomodulators a bendamustine-based treatment can be used as “salvage”.In this retrospective analysis we have identified 32 patients with R/R MM by means of case research, have been bendamustine-based treated at Hematological Clinics of Russian Federation since 2011. Median age was 67 (43–81) years, the female/male ratio was 2.5:1. After in median 2 (1–7) lines of prior therapy patients received in median 3 (1–9) cycles of bendamustine-based therapy. Bendamustine dosage was 70–120 mg/m2 /day on 2 days of each 28-day cycle until progressive disease or intolerability. Overall rate response was 56.2 %: 21.9 % partial response, stable disease 34.4 %. Median time to progression was 5.3 (0.8–18.0) months and median overall survival was 25.4 (0.8–47.1) months. Hematologic toxicity was in 53.2 % of patients.